Analisis Keamanan Instalasi Listrik Penerangan dan Pompa Air di Wilayah Perkampungan - Ruwah Joto; Harrij Mukti K.; Tresna Umar Syamsuri; Wijaya Kusuma; Rahma Nur Amalia (Politeknik Negeri Malang, 2020)
The use of lighting installations installed in the RW VIII Kelurahan Kesatrian has various aspects in terms of installation and use. To prevent losses due to the installation, the solution is to conduct electrical installationtraining. As a result of this training, it is hoped that the community can make efforts to install lighting or independentlyin their respective homes safely and correctly. The purpose of this Community Service is to provide knowledge andskills in installing electrical installations correctly and safely, given the use of household electrical appliances withvarious brands, each brand of household electrical equipment has different reliability, and utilization and operationthat require safety for users.